THE VARIETY OF PROBLEMS IN JAPANESE STUDENTS’ HYPOTHETICAL PREMISE CONSTRUCTIONS: Received: 11th August 2023; Revised: 21st September 2023, 7th November 2023, 16th November 2023, 30th November 2023; Accepted: 14th August 2023 - Gann, David A. (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Among the foundations of critical thinking in EFL is the ability of language learners to be able to express their views in terms of predictions and outcomes. It is all the more important in science universities such as the institution where the author teaches. Nine Japanese first-year university students in Japan, participated in a study involving an extended experiential learning project, using physical objects and observable phenomena. While students’ general use of premise and conclusion markers markedly improved, problems in their construction of hypothetical premises persisted. I will discuss the types of problems and offer explanations for why these problems continue to occur, and I will suggest ways in which instruction on hypothetical premise construction may be improved.